Pembelajaran Aktif: Implementasi Pendekatan Experiential Learning Pada Pembelajaran IPA untuk Meningkatkan Hasil Belajar: Implementasi Pendekatan Experiential Learning Pada Pembelajaran IPA untuk Meningkatkan Hasil Belajar Siswa Materi Unsur Senyawa Campuran - Nurdiah, Renita Fuji; Budiyanto, Mohammad; Alima, Siti Aisyah (PendIPA Journal of Science Education, 2024)
This study aims to describe active learning through the implementation of experiential learning in improving student learning outcomes. The type of research is Classroom Action Research conducted over 3 learning cycles. Each learning cycle includes the stages of planning, implementation, observation, and reflection. The research subjects were students of class VIII D SMP Negeri 5 Pamekasan as many as 28 students. The research instruments used were test instruments in the form of concept understanding questions and field notes. The data analysis technique used descriptive analysis by calculating the average and percentage of classical completeness on the test of improving student learning outcomes in the three cycles. Student learning outcomes based on the percentage of student completeness increased in cycle 1 by 61% with an average of 66, cycle 2 by 75% with an average of 75 and cycle 3 by 93% with an average of 81. The results obtained from cycle 1, cycle, 2, and cycle 3 of active learning through experiential learning approach in science learning can be a reference for teachers or prospective teachers to improve student learning outcomes.